Rare c-KIT c.1926delA and c.1936T>G Mutations in Exon 13 Define Imatinib Resistance in Gastrointestinal Stromal Tumors and Melanoma Patients: Case Reports and Cell Experiments - Yan, Chi; Zhao, Chengzhi; Yang, Ke; Zhou, Hongyan; Jing, Limin; Zhao, Weixing; Dou, Wenguang; Xia, Qingxin; Ma, Jie; Wei, Bing; Guo, Yongjun (Frontiers in Molecular Biosciences, 2022)
Background: Target therapies play more and more important roles in gastrointestinal stromal tumors (GISTs) and melanoma with the advancement of clinical drugs that overcome the resistance caused by gene mutations. c-KIT gene mutations account for a large portion of GIST patients, which are known to be sensitive or resistant to tyrosine kinase inhibitors. However, the role rare mutations play in drug efficacy and progression-free duration remains elusive. Methods: Two rare mutations were identified using Sanger sequencing from the GIST and melanoma cases. Cell experiments were further carried out to demonstrate their role in the imatinib resistance. Results:c-KIT c.1926delA p.K642S*FS mutation in primary and recurrent GIST patients and c-KIT c.1936T>G p.Y646D point mutation in melanoma patients in exon 13 were first demonstrated to be novel targets resistant to imatinib agent. Conclusion:c-KIT mutations c.1926delA and c.1936T>G in exon 13 are clinically significant targets that exhibit resistance to imatinib. This study provides guidance to GIST and melanoma treatments.